PENGARUH LITERASI KEUANGAN, PENGETAHUAN INVESTASI, DAN OVERCONFIDENCE TERHADAP KEPUTUSAN INVESTASI MAHASISWA DI KOTA BATAM - kervin kervin; Argo Putra Prima (LPPM Universitas Putera Batam, 2026)
The development of financial technology has facilitated access for the public, including students, to invest through various instruments, both in the capital market and digital platforms. However, many students are still unaware of or even indifferent to the ease and importance of investing for the future. This study aims to analyze the factors influencing individual investors in making investment decisions. The factors examined in this study include financial literacy, investment knowledge, and overconfidence. The approach used is a quantitative approach, by directly distributing questionnaires to primary data. The sample in this study was calculated using the Slovin formula, resulting in 100 respondents using the simple random sampling method. The data available in this study were analyzed using descriptive statistical analysis, instrument testing, classical assumption testing, influence testing, hypothesis testing, and coefficient of determination analysis using SPSS version 31 as a data processing tool. The results of the study indicate that Financial Literacy, Investment Knowledge, and Overconfidence partially and simultaneously influence Investment Decisions. Therefore, all hypotheses in this study are accepted.